2011
DOI: 10.3748/wjg.v17.i33.3830
|View full text |Cite
|
Sign up to set email alerts
|

YKL-40 expression in CD14+liver cells in acute and chronic injury

Abstract: Hepatic CD14⁺ cells are an YKL-40 mRNA and protein source in acute and chronic liver injury, with expression patterns similar to growth factors implicated in inflammation-fibrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Its level in cirrhotic patients was significantly higher compared to CHC cases (p < 0.01). These results are in agreement with other studies ( 9 , 53 , 54 , 61 ). Rath et al ( 62 ) suggested that YKL-40 was a powerful fibrosis marker with high diagnostic accuracy, particularly in HCV-associated liver disease.…”
Section: Discussionsupporting
confidence: 94%
“…Its level in cirrhotic patients was significantly higher compared to CHC cases (p < 0.01). These results are in agreement with other studies ( 9 , 53 , 54 , 61 ). Rath et al ( 62 ) suggested that YKL-40 was a powerful fibrosis marker with high diagnostic accuracy, particularly in HCV-associated liver disease.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, elevated YKL-40 was found in a vast array of inflammatory diseases that contain bacterial infections (Kronborg et al, 2002), rheumatoid arthritis (Nielsen et al, 2011), osteoarthritis (Volck et al, 2001), hepatic fibrosis (Pizano-Martinez et al, 2011), and hepatitis (Johansen et al, 2000; Fontana et al, 2010), asthma and chronic obstructive pulmonary diseases (Park et al, 2010), neuroinflammation (Bonneh-Barkay et al, 2010), and bowel lesion (Vind et al, 2003). In the chronic inflammatory diseases, YKL-40 is appreciated to mediate infiltration, differentiation, and maturation of macrophages, the primary leukocytes in response to inflammation (Boot et al, 1995; Rehli et al, 1997; Renkema et al, 1998; Rehli et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is produced by multiple cell types, including neutrophils, macrophages (MΦ), chondrocytes, synovial cells, smooth muscle cells, endothelial cells, and tumor cells . Increased levels of Chi3l1 have been correlated with poor prognosis in liver diseases, such as hepatic fibrosis, nonalcoholic fatty liver, alcoholic liver disease, and hepatocellular carcinoma . However, the biological functions of Chi3l1 in the liver remain mysterious.…”
mentioning
confidence: 99%
“…(16,17) Increased levels of Chi3l1 have been correlated with poor prognosis in liver diseases, such as hepatic fibrosis, nonalcoholic fatty liver, alcoholic liver disease, and hepatocellular carcinoma. (18,19) However, the biological functions of Chi3l1 in the liver remain mysterious. Our study indicates that Chi3l1 plays a critical role in promoting IAOC and liver injury through inducing tissue factor (TF) expression via mitogen-activated protein kinase (MAPK) activation.…”
mentioning
confidence: 99%